The p38 MAPK pathway inhibits tristetraprolin-directed decay of interleukin-10 and pro-inflammatory mediator mRNAs in murine macrophages. - Tudor, C; Marchese, F; Hitti, E; Aubareda, A; Rawlinson, L; Gaestel, M; Blackshear, P; Clark, A; Saklatvala, J; Dean, J (2009)
p38 mitogen-activated protein kinase (MAPK) stabilises pro-inflammatory mediator mRNAs by inhibiting AU-rich element (ARE)-mediated decay. We show that in bone-marrow derived murine macrophages tristetraprolin (TTP) is necessary for the p38 MAPK-sensitive decay of several pro-inflammatory mRNAs, including cyclooxygenase-2 and the novel targets interleukin (IL)-6, and IL-1alpha. TTP(-/-) macrophages also strongly overexpress IL-10, an anti-inflammatory cytokine that constrains the production of the IL-6 despite its disregulation at the post-transcriptional level. TTP directly controls IL-10 mRNA stability, which is increased and insensitive to inhibition of p38 MAPK in TTP(-/-) macrophages. Furthermore, TTP enhances deadenylation of an IL-10 3'-untranslated region RNA in vitro.